Fuzzy relation equations for coding/decoding processes of images and videos - Loia, Vincenzo; Sessa, Salvatore (Information sciences, 2005)
We adopt fuzzy relation equations with continuous triangular norms for compression/decompression processes of grey images, colour images in the RGB space and frames of videos, by comparing the results of the reconstructed images with standard methods like JPEG and MPEG-4. Any image is subdivided in blocks and each block is coded/decoded using arbitrary fuzzy sets as coders in the fuzzy equations. We evaluate the peak signal to noise ratio (PSNR) on the decompressed images for several values of the compression rates as measure of the quality of images and frames reconstructed. The original frames of a video are classified in Intra-frames and Predictive frames by using a similarity measure based on the well known Lukasiewicz t-norm.